2019
DOI: 10.1007/s11248-019-00160-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential impacts associated with gene flow from transgenic hybrids to Mexican maize landraces

Abstract: Genetically modified (GM) maize has been grown and safely consumed on a global scale since its commercialization in 1996. However, questions have been raised about the potential impact that GM maize could have on native maize landraces in Mexico, which is the center of origin and diversity of maize. This research was conducted to evaluate potential changes to maize landraces in an unlikely event of transgene introgression. For this study, two GM traits that confer insect protection and herbicide tolerance in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(70 reference statements)
1
9
0
1
Order By: Relevance
“…Many studies report that the mode of transgene inheritance follows directly a Mendelian segregation pattern [ 54 57 ] In maize, Duncan et al [ 58 ] reported that after GM traits were introgressed into landrace maize varieties the transgene segregated like other endogenous genes, following Mendelian principles,. In contrast, non-Mendelian segregation of transgenes has been reported in studies on rice [ 59 ], soybean [ 60 ], tobacco [ 61 ], wheat [ 62 ] and cotton [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies report that the mode of transgene inheritance follows directly a Mendelian segregation pattern [ 54 57 ] In maize, Duncan et al [ 58 ] reported that after GM traits were introgressed into landrace maize varieties the transgene segregated like other endogenous genes, following Mendelian principles,. In contrast, non-Mendelian segregation of transgenes has been reported in studies on rice [ 59 ], soybean [ 60 ], tobacco [ 61 ], wheat [ 62 ] and cotton [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study with yellow and white maize hybrids, a similar range of 4.4–5.16 μg/g dw was found ( 35 ). In hybrids derived by crossing a genetically modified parent with landraces, ranges were observed between 55.6 and 123.6 μg/g dw ( 32 ). However, further studies of specialty maize have found a higher value of soluble trans -ferulic acid in these varieties, especially in sweet corn ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al ( 42 ) found that conventional hybrids contained a range of 84.79–239.33 μg/g dw, Venkatesh et al ( 43 ) found 232.58–532.51 μg/g dw, Harrigan et al ( 44 ) reported 84.15–259.68 μg/g dw, whereas the values in Classen et al ( 45 ) fluctuated between 29.3 and 219 μg/g dw. Duncan et al ( 32 ) reported that genetically modified hybrids crossed with landraces have ranges between 101.9 and 236.2 μg/g dw. The ILSI database covers most of these ranges and is a reliable alternative for comparison of bound p -coumaric acid ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations